2018
DOI: 10.1002/clc.22914
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in the prognostic utility of left ventricular mass index for incident cardiovascular disease

Abstract: Background: Evidence exists for racial/ethnic differences in left ventricular mass index (LVMI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…report greater prognostic utility of LVMi for predicting cardiovascular events for Chinese and Hispanic populations in comparison to non-Hispanic Whites. 38 Similarly, there are reports of significant ethnic differences in ventricular remodelling in response to important cardiovascular risk factors such as hypertension. 36 As ethnic variation exist for LV parameters, it is possible that there are also ethnic differences in the morphology of other cardiac chambers (right ventricle, atria).…”
Section: Discussionmentioning
confidence: 99%
“…report greater prognostic utility of LVMi for predicting cardiovascular events for Chinese and Hispanic populations in comparison to non-Hispanic Whites. 38 Similarly, there are reports of significant ethnic differences in ventricular remodelling in response to important cardiovascular risk factors such as hypertension. 36 As ethnic variation exist for LV parameters, it is possible that there are also ethnic differences in the morphology of other cardiac chambers (right ventricle, atria).…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 In addition, there might also be ethnic differences regarding the relationship between LVH and poor cardiovascular outcomes. 12 , 13 Existing evidence suggests that the relationship between LVH and poor cardiovascular outcomes is strongest among Chinese and Hispanics compared with non‐Hispanic Whites. 13 This could imply that Chinese and Hispanics might benefit more from a risk prediction model for LVH.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Existing evidence suggests that the relationship between LVH and poor cardiovascular outcomes is strongest among Chinese and Hispanics compared with non‐Hispanic Whites. 13 This could imply that Chinese and Hispanics might benefit more from a risk prediction model for LVH. Nevertheless, to the best of knowledge there are no LVH risk prediction models aimed at Chinese hypertensives.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, evidence for racial differences. Akintoye et al [82] found that the relationship between LV mass and incident cardiovascular disease was strongest among Chinese and Hispanics, and weakest for non-Hispanic Whites.…”
Section: Imaging Biomarkers and Outcome Predictionsmentioning
confidence: 99%
“…These approaches have allowed to characterize early changes in cardiac phenotypes and to find novel associations with cardiac risk factors [5]. Further, they have helped to prognosticate long-term outcomes based on specific imaging biomarkers [6]. This review describes the use of CMR across large-scale prospective population studies, highlights novel associations found in the setting of the wide application of those imaging techniques, and discusses novel automated image analysis strategies to overcome challenges posed by the large amount of data obtained in population-based studies.…”
Section: Introductionmentioning
confidence: 99%